2023
DOI: 10.1097/gme.0000000000002150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ospemifene on vaginal microbiome in postmenopausal women with vulvovaginal atrophy

Abstract: Objectives: This study aimed (i) to compare the vaginal microbiome profiles of women suffering from vulvovaginal atrophy with that of healthy postmenopausal women and to (ii) assess the effect of ospemifene and systemic hormone treatment on the composition of the vaginal microbiome.Methods: Sixty-seven postmenopausal women attending the Gynecology Clinic of Azienda Ospedaliero-Universitaria of Bologna (Italy) were enrolled. Of them, 39 received a diagnosis of atrophy and 28 were considered healthy controls. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A higher VMI (reflective of more superficial cells and a thicker vaginal epithelium) has been associated with higher relative abundance of Lactobacillus spp. 21 Vaginal pH reliably increases as serum estradiol levels decrease in menopause. Lactobacillus species produce lactic acid, which may play an antimicrobial role to protect against pathogen colonization.…”
Section: Physical Findings Of Gsm (Vulvovaginal Atrophy) and Associat...mentioning
confidence: 99%
See 3 more Smart Citations
“…A higher VMI (reflective of more superficial cells and a thicker vaginal epithelium) has been associated with higher relative abundance of Lactobacillus spp. 21 Vaginal pH reliably increases as serum estradiol levels decrease in menopause. Lactobacillus species produce lactic acid, which may play an antimicrobial role to protect against pathogen colonization.…”
Section: Physical Findings Of Gsm (Vulvovaginal Atrophy) and Associat...mentioning
confidence: 99%
“…15 A comparison of people with VVA being treated with oral estrogen and the selective estrogen receptor modulator ospemifene showed that both had higher relative abundance of Lactobacillus than untreated participants. 21 Lastly, although not an randomized controlled trial, a comparison of people on tibolone therapy versus no treatment demonstrated that people on tibolone had a higher relative abundance of Lactobacillus. 25 Topical vaginal estrogen is also associated with a change in microbiome composition.…”
Section: The Impact Of Hormone Therapy On the Vaginal Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Alvisi et al 12 made two comparisons of the vaginal microbiota: (1) between healthy postmenopausal controls (n = 28) and people with vulvovaginal atrophy (VVA) on examination (n = 39), and (2) between pretreatment and posttreatment samples among women with VVA who received either systemic hormonal therapy (HT) (n = 19) or ospemifene (n = 20). 13 The authors specifically excluded people with primarily urinary symptoms, which is why they did not use the term genitourinary syndrome of menopause. At baseline, they demonstrated significantly different alpha and beta diversity between healthy controls and people with VVA.…”
mentioning
confidence: 99%